ROLE TEACHER IN DEVELOPING STUDENT SOCIAL SKILLS IN SDN 2 SUMBERSARI DURING THE COVID 19 PANDEMIC (Joyful Learning Journal, 2022)
The purpose of the study was to find out how teachers at SDN 2 Sumbersari developed students' social skills during the Covid 19 pandemic, to find out the obstacles and efforts of teachers at SDN 2 Sumbersari in developing students' social skills during the Covid 19 pandemic. This research used a qualitative research design. The main data source is the informant, the data source is obtained from interviews. Sources of data obtained from research informants, namely: principals and teachers. Data collection techniques in this study utilize the methods of observation, interviews, and documentation. Researchers checked the validity of the data using source triangulation. Data analysis techniques are: data collection, data reduction, data presentation, and data verification. The results of the study indicate the role of the teacher as a guide and facilitator in order to develop the social skills of SDN 2 Sumbersari students during the pandemic, namely through planning embodied in the RPP which includes activities that involve students and in its implementation gives students the freedom to communicate and exchange opinions through chat room media. those on Google Meet or Whatsapp groups, in the evaluation activities, it is preferred to use an oral exam via video call.